Evaluation of fungicides as protective and curative treatments against canker disease of Eucalyptus urograndis in Sarawak, Malaysia - Ambrose, Annya (2024)
Plantations of the genus Eucalyptus L’Hér have rapidly expanded in Sarawak, Malaysia, accounting for 19% of the total forest plantation area. In a routine forest health surveillance conducted in 2022 at Sarawak, Malaysia, tree stands of the hybrid between Eucalyptus grandis x Eucalyptus urophylla hybrid better known as Eucalyptus urograndis were detected with symptoms of stem canker disease caused by Chrysoporthe infection. Given the limited information on the chemical control of Chrysoporthe stem canker disease, there is a growing need to develop effective chemical control strategies to protect and cure Chrysoporthe infection on E. urograndis trees. Therefore, this study aimed to identify the causal pathogen of this stem canker disease in E. urograndis stands in Sarawak, Malaysia, and evaluate the efficacy of various fungicides as curative and protectant treatments on canker infection using artificial inoculation methods. All isolates were first collected and subjected to molecular identification and pathogenicity analysis. The inhabitation efficacy of five licensed fungicides: thiram, prochloraz manganese chloride, copper hydroxide, dimethomorph, and mancozeb against the disease pathogen was evaluated through an in vitro test. The performance of these fungicides was then assessed through protective and curative field experiments on 10-yearold E. urograndis trees using the artificial inoculation technique. The isolates were identified as Chrysoporthe deuterocubensis based on morphology and through comparisons of DNA sequence data from the ITS1/ITS4, β-tubulin 2 gene regions. Isolate CHRY18 recorded the highest virulence based on the pathogenicity test. The in-vitro efficacy tests showed that prochloraz manganese chloride achieved 100% inhibition against C. deuterocubensis at 1.0 mg/mL. Thiram significantly inhibited C. deuterocubensis infection in the protective experiment, yielding the shortest lesion length (19.40 mm) compared to the non-treated control (47.48 mm) at 20 weeks post-inoculation. In the curative experiment, a reduction of 54.7% in lesion length was observed in inoculated symptomatic trees after 20 weeks of post-fungicide treatment by copper hydroxide. In conclusion, this study demonstrated that the combination of prochloraz manganese chloride and copper hydroxide could be utilised an as effective chemical control of C. deuterocubensis stem canker on E. urograndis.